Outcomes after eye‐sparing surgery vs orbital exenteration in patients with lacrimal gland carcinoma. Issue 5 (11th February 2020) - Bonavolontà, Paola; Esmaeli, Bita; Donna, Piero; Tranfa, Fausto; Iuliano, Adriana; Abbate, Vincenzo; Fossataro, Federica; Attanasi, Federica; Bonavolontà, Giulio
Abstract: Background: This study examined whether eye‐sparing surgery is associated with better or worse outcomes than exenteration for the treatment of lacrimal gland carcinomas. Methods: Forty‐six patients treated for lacrimal gland carcinoma were retrospectively reviewed and compared. A statistical analysis was performed using Kaplan‐Meier plots. Results: The overall survival rates for eye‐sparing surgery were 52% and 37% at 5 and 10 years, and those for exenteration were 37% and 25% at 5 and 10 years, respectively ( P = .73). The proportion of patients with local regional control at both 5 and 10 years after eye‐sparing surgery was 0.75, and that for exenteration was 0.47 ( P = .30). For eye‐sparing surgery, the proportions of distant metastasis‐free survival at 5 and 10 years were 0.51 and 0.39 for eye‐sparing surgery and 0.29 and 0.14 for exenteration ( P = .50). Conclusion: Because the outcomes were not significantly different, the authors suggest that eye‐sparing surgery can be proposed as a reasonable approach for lacrimal gland carcinomas in appropriately selected patients.